Elevated levels of circulating cell-free DNA and neutrophil proteins are associated with neonatal sepsis and necrotizing enterocolitis in immature mice, pigs and infants. Issue 6 (August 2017) - Nguyen, Duc Ninh; Stensballe, Allan; Lai, Jacqueline CY; Jiang, Pingping; Brunse, Anders; Li, Yanqi; Sun, Jing; Mallard, Carina; Skeath, Tom; Embleton, Nicholas D; Berrington, Janet E; Sangild, Per T
Preterm infants are highly susceptible to late-onset sepsis (LOS) and necrotizing enterocolitis (NEC), but disease pathogenesis and specific diagnostic markers are lacking. Circulating cell-free DNA (cfDNA) and immune cell-derived proteins are involved in multiple immune diseases in adults but have not been investigated in preterm neonates. We explored the relation of circulating neutrophil-associated proteins and cfDNA to LOS and/or NEC. Using a clinically relevant preterm pig model of spontaneous LOS and NEC development, we investigated neutrophil-associated proteins and cfDNA in plasma, together with cytokines in gut tissues. The changes in cfDNA levels were further studied in preterm pigs and neonatal mice with induced sepsis, and in preterm infants with or without LOS and/or NEC. Fifteen of 114 preterm pigs spontaneously developed both LOS and NEC, and they showed increased intestinal levels of IL-6 and IL-1β and plasma levels of cfDNA, neutrophil-associated proteins, and proteins involved in platelet-neutrophil interaction during systemic inflammation. The abundance of neutrophil-associated proteins highly correlated with cfDNA levels. Further, Staphylococcus epidermidis challenge of neonatal mice and preterm pigs increased plasma cfDNA levels and bacterial accumulation in the spleen. In infants, plasma cfDNA levels were elevated at LOS diagnosis and 1–6 d before NEC. In conclusion, elevated levels of plasma cfDNA and neutrophil proteins are associated with LOS and NEC diagnosis.